PENGARUH PENGGUNAAN MEDIA AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA - Acesta, Arrofa; Nurmaylany, Milla (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2018)
In this study discusses the effect of using augmented reality media on student learning outcomes in class IV in Natural Sciences (IPA) where the problem in this study is that student learning outcomes for Natural Sciences subjects are still low. Because of the lack of use of varied media so that it makes less communication between teachers who provide knowledge with students who receive knowledge become less understanding and less interested in the learning delivered. Because the basis of students' lack of interest in learning, ultimately contributes to the learning outcomes. The purpose of this study is to find out whether there are differences in learning outcomes between classes that use augmented reality learning media with class learning outcomes that use two-dimensional media images before treatment (pretest), after treatment (posttest) and differences in gain of learning outcomes. The research method in this study was an experimental method, carried out at SD 1 Karangtawang, Kuningan District. With a sample consisting of class IV A as an experimental class with 21 students and IV B as a control class with 20 students. Data collection techniques used are documentation and tests. Data obtained were then analyzed using statistical tests including normality test, homogeneity test and hypothesis test (t-test). The conclusion from the results of this study that the learning outcomes of students who use augmented reality learning media produce tcount 4.83> ttable 2.02, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. With the acceptance of Ha, it can be concluded that there is an influence of the use of augmented reality media on science learning outcomes.